Pengembangan Media Komik dengan Nilai Karakter pada Materi Sumpah Pemuda Kelas V di SDN 2 Kelekar - Rizal, Samsu; Arafat, Yasir; Heldayani, Eni (Universitas Batanghari Jambi, 2024)
This research aims to produce comic civics learning media on youth oath material in Class V Elementary Schools that is valid and practical. This research uses the Research and Development method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results of data analysis show that the comic media developed is in the